Media Systems of South-Eastern Europe in the Condition of Democratic Transition: The Example of Albania, Bulgaria, Macedonia and Serbia - Elena Savova Georgieva; Yulia Socratovna Danilova; Aleksei Yuryevich Bykov; Anna Smoliarova Sergeevna; Nikolai Sergeevich Labush (International Review of Management and Marketing, 2015)
The region of South-Eastern Europe is unique in that it can demonstrate us all the stages of democratic transition, starting from the first democratic reforms in the 90-ies of XX century and down to accession to the European Union. The article describes the transformation occurred in the media systems of Albania, Bulgaria, Macedonia, and Serbia, and also the main results achieved in the process of democratic transition are revealed. Nowadays it is obvious that these countries face many problems during the transition. National media systems demonstrate a high degree of political parallelism and economic marginality.  The South-Eastern European media are focused on covering political life, their political involvement is much stronger than in other European countries. As a result the media became an instrument of the political power, today it is hard to draw a line between political and journalistic activity. Another problem is the high level of political extremism in mass media. The article also describes the negative effects that currently hinder the integration of the media in the studied countries into the European information space. The study takes into account various domestic and external factors, influencing the development of media environment in the Balkan States.